ChemInform Abstract: Chemoselective Arylation of Phenols with Bromo‐nitroarenes: Synthesis of Nitro‐biaryl‐ols and Their Conversion into Benzofurans and Carbazoles. Issue 3 (January 2015) - Kumar, Amit; Yadav, Abhimanyu; Verma, Ajay; Jana, Sadhan; Sattar, Moh.; Kumar, Shailesh; Prasad, Ch. Durga; Kumar, Sangit
Abstract A mild method is developed for the construction of the title compounds tolerating diverse functional groups.